Epidemiology and seasonal dynamics of Ixodid ticks of dairy animals of Punjab state, India* - HAQUE, M; JYOTI, JYOTI; SINGH, N K; RATH, S S; GHOSH, S (The Indian Journal of Animal Sciences, 2011)
Cattle (890) and buffaloes (636) were examined from 8 districts of Punjab state, India with an overall prevalence of 85.28 and 57.10% Rhipicephalus (Boophilus) microplus, 20.45 and 52.20% Hyalomma anatolicum anatolicum and 5.73 and 9.90% mixed infestation in cattle and buffalo population, respectively. R. microplus was the predominant tick in cattle population (85.28%), whereas in buffalo population R. microplus and H. a. anatolicum were almost evenly distributed. Among the different agro-climatic zones a significantly higher prevalence of H. a. anatolicum was recorded in both cattle and buffalo population of Western Plain and Western regions with comparison to other regions i.e. Central Plain and Undulating Plains of the state. H. a. anatolicum was recorded more in summer (23.1%) and monsoon (21.0%) seasons compared to winter (6.10%). In cattle, the tick infestation was similar in both the sexes whereas in buffalo, R. microplus was predominating in males and H. a. anatolicum was predominating in females. In organized dairy farms, the prevalence of H. a. anatolicum was very low (3.74%) but was and higher (45.31%) in unorganized sector.